2017
DOI: 10.1155/2017/5197567
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anti‐Inflammatory Activities of Resveratrol through Classic Models in Mice and Rats

Abstract: Background. Inflammation and pain are closely related to humans' and animals' health. Resveratrol (RSV) is a natural compound with various biological activities. The current study is aimed to evaluate the analgesic and anti-inflammatory activities of RSV in vivo. Materials and Methods. The analgesic effects were assessed by the acetic acid-induced writhing and hot plate tests. The anti-inflammatory effects were determined using the xylene-induced mouse ear oedema, the acetic acid-induced rat pleurisy, and carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
(27 reference statements)
2
16
0
1
Order By: Relevance
“…In the present study, 90 days of resveratrol use resulted in a significant improvement in the clinical scores of OA pain and disability in participants with knee OA. These clinical observations are in line with the available data showing that resveratrol reduces pain, inflammation, and oedema, as well as articular destruction in experimental models of arthritis (Wang, Chen, Wang, 2016;Wang et al, 2017). Together with the previously reported data, the present finding supports the analgesic activity of dietary polyphenols in patients with mild-tomoderate knee pain, and suggests that it is in tune with the results of many pilot studies reported regarding the adjuvant use of polyphenols and other supplements during the treatment of inflammatory musculoskeletal disorders like knee OA and rheumatoid arthritis (Hussain et al, 2009;Hussain et al, 2016).…”
Section: Discusionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, 90 days of resveratrol use resulted in a significant improvement in the clinical scores of OA pain and disability in participants with knee OA. These clinical observations are in line with the available data showing that resveratrol reduces pain, inflammation, and oedema, as well as articular destruction in experimental models of arthritis (Wang, Chen, Wang, 2016;Wang et al, 2017). Together with the previously reported data, the present finding supports the analgesic activity of dietary polyphenols in patients with mild-tomoderate knee pain, and suggests that it is in tune with the results of many pilot studies reported regarding the adjuvant use of polyphenols and other supplements during the treatment of inflammatory musculoskeletal disorders like knee OA and rheumatoid arthritis (Hussain et al, 2009;Hussain et al, 2016).…”
Section: Discusionsupporting
confidence: 88%
“…Together with the previously reported data, the present finding supports the analgesic activity of dietary polyphenols in patients with mild-tomoderate knee pain, and suggests that it is in tune with the results of many pilot studies reported regarding the adjuvant use of polyphenols and other supplements during the treatment of inflammatory musculoskeletal disorders like knee OA and rheumatoid arthritis (Hussain et al, 2009;Hussain et al, 2016). Although the exact mechanism behind the impact of resveratrol on improving OA symptoms in a clinical setting has not been well described, a series of animal experiments conducted in the past few years has demonstrated that the oral administration of resveratrol is capable of significantly preventing the progression of osteoarthritis (Gu et al, 2016), and also exhibits a potent analgesic effect in different animal models (Wang et al, 2017;Bazzo et al, 2013). Despite the large output of preclinical studies dealing with the analgesic and antiinflammatory activities of resveratrol, there is a relative lack of clinical trials investigating the analgesic effect of resveratrol (Nguyen et al, 2017;Vang et al, 2011).…”
Section: Discusionmentioning
confidence: 99%
“…RES is a natural compound with multiple biological activities. A previous study reported that RES could inhibit various pain and inflammation conditions and able to exert a treatment effect with analgesic and anti-inflammatory activities [30]. Exercise-induced muscle damage (EIMD) can cause pain and affect daily activities, such as reduced range of motion, stiffness and swelling [31].…”
Section: Discussionmentioning
confidence: 99%
“…8 , 9 It has been widely reported that resveratrol has anti-proliferative, anti-oxidative, anti-inflammatory, and analgesic effects in many experimental models. 10 14 Preclinical studies provided accumulating evidence on its efficacy in ameliorating the degenerative articular damage that mostly attributed to its pleiotropic properties. 15 , 16 Moreover, many pieces of evidence have displayed resveratrol as one of the nutraceutical candidates for OA therapy in human.…”
Section: Introductionmentioning
confidence: 99%